An interesting new record of Egyptian locust Anacridium aegyptium (Linnaeus, 1764) (Orthoptera: Acrididae) for Slovenian inland - Jan Gojznikar; Nejc Poljanec; Matija Mlakar Medved (Natura Sloveniae)
n/a